QORAQALPOG‘ISTONDA MAKTAB TA’LIMI TIZIMINING RIVOJLANIShI VA JOYLAShUVI XUSUSIYATLARI - Uzakbaev, K.K.; Turgʻanbaev, D.N. (SCIENCE and SOCIETY, 2025)
The article describes the organization and distribution of the school education system in the Republic of Karakalpakstan.